Acute Myeloid Leukemia Presenting as Myeloid Sarcoma with a Predisposition to the Gynecologic Tract - Ryan M. Kahn; Sushmita Gordhandas; Eloise Chapman-Davis; Elizabeth Margolskee; Cathleen Matrai; Amy Chadburn; Ellen Ritchie (Case Reports in Oncological Medicine)
Myeloid sarcoma (MS) is a rare, extramedullary tumor consisting of immature white blood cells of myeloid lineage. MS is usually associated with the concurrent diagnosis of acute myeloid leukemia (AML) but can also present in the absence of bone marrow disease or at relapse of AML. MS of the gynecologic tract is exceedingly rare; however, it is hypothesized that it is likely more prevalent than previously understood given postmortem findings and persistence in preserved ovarian tissue. There is minimal literature surrounding MS and extramedullary relapse with no clear guidelines. This is a case report of a 48-year-old woman with MS involving the uterine corpus, fallopian tubes, and left ovary followed by a literature review. The overall aim is to review data regarding leukemic immune evasion and sanctuary sites in order to raise awareness as this represents an important and underrecognized hematologic malignancy in an often misdiagnosed, underrecognized site.